DAMPAK PENGEMBANGAN TANAMAN MELALUI TRANSGENIK TERHADAP LINGKUNGAN DI INDONESIA - Fakultas Pertanian UNISRI, Priyono (MAJALAH ILMIAH GEMA, 2002)
"Transgenik" is a part of genetic artifical (bio technology) by organism that hopefully use from and for humam interest. It applied scientific principles and artificial processing material (to supply commodity and service in order to be helpful for society and environment). To simplity therefore, genetic arfificial is one of the applications in bio technology, that means gene transplantion from one cell to another to rebuilt or make a new organism. There, what is the benefit and objective of transgenik method?Keyword: the impact of development, plants, transgenic,